High‐frequency gravity waves observed in the low‐latitude mesosphere‐lower thermosphere (MLT) region and their possible relationship to lower‐atmospheric convection - Kovalam, S.; Tsuda, T.; Gurubaran, S. (My University, 2011)
Observations of Medium Frequency (MF) radar winds made at Pameungpeuk (7.5°S, 107.5°E) and Tirunelveli (8.7°N, 78°E) between February and March 2010 are used to study gravity wave activity in the equatorial mesosphere and lower thermosphere (80–100 km). Gravity wave variances in the 20–120 min period band and their spectra are computed. Daily values of gravity wave variances show modulations on time scales ranging from diurnal to planetary waves. Spectra of wave variances display peaks at tidal periods and show evidence of gravity wave modulation at 24, 12, and 8 h periods. Statistical investigation of waves, made using Stokes parameter technique, indicates that the directionality of the mesospheric wave field is highly anisotropic. The role of lower‐atmospheric sources on the MLT gravity wave variability is also examined. Spatial distribution of cloud top temperature and rainfall rates are used. GW activity at mesosphere‐lower thermosphere (MLT) heights shows clear anticorrelation with the cloud top temperature and positive correlation with rainfall rates suggesting a possible link between observed gravity wave variability and the variations in the deep tropical convection.
Keywords: MLT region; Gravity waves; Middle atmosphere; MF radar; Pameungpeuk; Tirunelveli; Medium Frequency Radar; PRR; Partial Reflection Radar